METILFENIDATO EM CRIANÇAS COM DIAGNÓSTICO DE TDAH: CONSIDERAÇÕES PARA PAIS E EDUCADORES - SCHON, VIVIANE DE JESUS (2022)
ADHD is a neurobiological disorder, of genetic causes, that often accompanies the child throughout his life, being characterized by distraction and difficulty concentrating, in addition to hyperactivity and impulsivity. The reported symptoms lead to negative consequences, interfering with the psyche, memory, family and social relationships, and later, professional life. This work is a systematic literature review, of a qualitative nature, aims to investigate the literature on the use of methylphenidate in the treatment of ADHD, in the period between 2011 and 2020, review empirical studies of reported reactions associated with the use of the drug and collaborate to define better pedagogical interventions, collaborating with parents and teachers. The methods for this systematic review/meta-analysis were developed in accordance with the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-analyses. in the search strategy we included published data pertinent to our inclusion and exclusion criteria (Figure 1.). Electronic databases were searched without language, date and document type restrictions: As of 2011. Foreign databases were searched with the translated search strategy. The search strategy/syntax was adapted for each database. Data extraction: Studies were identified through electronic searches. Outcomes assessed included ADHD symptoms, serious adverse events, non-serious adverse events, general behavior, and quality of life. We use standard methodological procedures expected at Cochrane. Results from meta-analyses suggest that methylphenidate may improve symptoms, general behavior, and quality of life reported by parents and teachers among children and adolescents diagnosed with ADHD. However, the low quality of the evidence means that we cannot be sure of the effects. In the short follow-up periods of the included studies, there is evidence that methylphenidate is associated with an increased risk of adverse events such as sleep problems and decreased appetite. Long-term follow-up research is needed to assess the benefits of methylphenidate. The conclusions point to the lack of long studies on adverse reactions caused by the drug. And that methylphenidate improves attentional control and sustained attention, but has no effects on selective attention or working memory.